Physical Disturbance by Bottom Trawling Suspends Particulate Matter and Alters Biogeochemical Processes on and Near the Seafloor - Bradshaw, Clare; Jakobsson, Martin; Brüchert, Volker; Bonaglia, Stefano; Mörth, Carl-Magnus; Muchowski, Julia; Stranne, Christian; Sköld, Mattias (Frontiers in Marine Science, 2021)
Bottom trawling is known to affect benthic faunal communities but its effects on sediment suspension and seabed biogeochemistry are less well described. In addition, few studies have been carried out in the Baltic Sea, despite decades of trawling in this unique brackish environment and the frequent occurrence of trawling in areas where hypoxia and low and variable salinity already act as ecosystem stressors. We measured the physical and biogeochemical impacts of an otter trawl on a muddy Baltic seabed. Multibeam bathymetry revealed a 36 m-wide trawl track, comprising parallel furrows and sediment piles caused by the trawl doors and shallower grooves from the groundgear, that displaced 1,000 m3 (500 t) sediment and suspended 9.5 t sediment per km of track. The trawl doors had less effect than the rest of the gear in terms of total sediment mass but per m2 the doors had 5× the displacement and 2× the suspension effect, due to their greater penetration and hydrodynamic drag. The suspended sediment spread >1 km away over the following 3–4 days, creating a 5–10 m thick layer of turbid bottom water. Turbidity reached 4.3 NTU (7 mgDW L–1), 550 m from the track, 20 h post-trawling. Particulate Al, Ti, Fe, P, and Mn were correlated with the spatio-temporal pattern of suspension. There was a pulse of dissolved N, P, and Mn to a height of 10 m above the seabed within a few hundred meters of the track, 2 h post-trawling. Dissolved methane concentrations were elevated in the water for at least 20 h. Sediment biogeochemistry in the door track was still perturbed after 48 h, with a decreased oxygen penetration depth and nutrient and oxygen fluxes across the sediment-water interface. These results clearly show the physical effects of bottom trawling, both on seabed topography (on the scale of km and years) and on sediment and particle suspension (on the scale of km and days-weeks). Alterations to biogeochemical processes suggest that, where bottom trawling is frequent, sediment biogeochemistry may not have time to recover between disturbance events and elevated turbidity may persist, even outside the trawled area.